`log_2 (x) + log_2 (x + 2) = log_2 (x + 6)` Solve the logarithmic equation algebraically. Approximate the result to three decimal places.

1 Answer

loves2learn's profile pic

loves2learn | (Level 3) Salutatorian

Posted on

Since they are both `log_2 ` , rewrite it using properties of logs

`log_(2)(x)(x+2)=log_2(x+6) `

Exponentiate both sides by 2 and solve for x

`2^(log_(2)(x)(x+2))= 2^(log_2(x+6))`

`x(x+2)=x+6 `

`x^2+x-6=0 `

`(x+3)(x-2)=0 `

`x=-3 ` and `x=2 `

Since you cannot take the log of a negative number, `x=-3 ` is not viable.

Therefore, your answer is `x=2 `